A imagem dos índios brasileiros: um contraste de olhares entre o cinema nacional e a série vídeo nas aldeias - Sampaio, Cybelle Saraiva (2010)
The present thesis has a special interest in analyzing the making of the image of the Brazilian Indians as presented in domestic cinematography and videography. Here the mythical image of these people is discussed as it appears in two films: O Guarani (1996), by Norma Bengell and Caramuru, a invenção do Brasil (2001), by Guel Arraes, and in documentary videos selected from the series Vídeo nas Aldeias, in order to compare contrasting views on the Indians. For such goals this work revisits concepts familiar to authors like Lévi-Strauss and Roland Barthes, who illuminate issues on the building of the mythical discourse; Pierre Bourdieu and Charles Sanders Pierce, who postulate the notions of creed as habits of action, in addition to other authors, who think the notion of culture under an anthropological perspective